Ranking of Logistics System Scenarios for Central Business District - Tadić, Snežana Radoman; Zečević, Slobodan Marko; Krstić, Mladen Dragan (Promet - Traffic&Transportation, 2014)
This paper presents the procedure for logistics system scenario selection for the central business district (CBD) of the city in the phase of significant urban changes. Scenarios are defined in accordance with the overall logistics concept of the city. Conflicting goals of stakeholders (residents, shippers and receivers, logistics providers and city government) generate a vast number of criteria that need to be included when selecting the scenario for the city area logistics system. Due to limited resources and linguistic assessment of criteria, fuzzy extensions of conventional multi-criteria decision-making (MCDM) methods were used. Fuzzy 'analytical hierarchy process' (FAHP) is applied to determine the relative weights of evaluation criteria, and fuzzy 'technique for order preference by similarity to ideal solution' (FTOPSIS) is applied to rank the logistics systems scenarios. This paper contributes to the literature in the field of city logistics (CL), as it applies the integrated FAHP-FTOPSIS method for the evaluation of scenarios, which are also integrated combinations of different CL initiatives. The integrated combined approach proved to be accurate, effective and a systematic tool for the decision support in the process of selecting CBD logistics scenarios.